Cutting-Edge Technology for Rapid Bedside Assessment of Capillary Refill Time for Early Diagnosis and Resuscitation of Sepsis - Sheridan, David C.; Cloutier, Robert; Kibler, Andrew; Hansen, Matthew L. (Frontiers in Medicine, 2020)
Sepsis currently affects over 30 million people globally with a mortality rate of ~30%. Prompt Emergency Department diagnosis and initiation of resuscitation improves outcomes; data has found an 8% increase in mortality for every hour delay in diagnosis. Once sepsis is recognized, the current Surviving Sepsis Guidelines for adult patients mandate the initiation of antibiotics within 3 h of emergency department triage as well as 30 milliliters per kilogram of intravenous fluids. While these are important parameters to follow, many emergency departments fail to meet these goals for a variety of reasons including turnaround on blood tests such as the serum lactate that may be delayed or require expensive laboratory equipment. However, patients routinely have vital signs assessed and measured in triage within 30 min of presentation. This creates a unique opportunity for implementation point for cutting-edge technology to significantly reduce the time to diagnosis of potentially septic patients allowing for earlier initiation of treatment. In addition to the practical and clinical difficulties with early diagnosis of sepsis, recent clinical trials have shown higher morbidity and mortality when septic patients are over-resuscitated. Technology allowing more real time monitoring of a patient's physiologic responses to resuscitation may allow for more individualized care in emergency department and critical care settings. One such measure at the bedside is capillary refill. This has shown favor in the ability to differentiate subsets of patients who may or may not need resuscitation and interpreting blood values more accurately (1, 2). This is a well-recognized measure of distal perfusion that has been correlated to sepsis outcomes. This physical exam finding is performed routinely, however, there is significant variability in the measurement based on who is performing it. Therefore, technology allowing rapid, objective, non-invasive measurement of capillary refill could improve sepsis recognition compared to algorithms that require lab tests included lactate or white blood count. This manuscript will discuss the broad application of capillary refill to resuscitation care and sepsis in particular for adult patients but much can be applied to pediatrics as well. The authors will then introduce a new technology that has been developed through a problem-based innovation approach to allow clinicians rapid assessment of end-organ perfusion at the bedside or emergency department triage and be incorporated into the electronic medical record. Future applications for identifying patient decompensation in the prehospital and home environment will also be discussed. This new technology has 3 significant advantages: [1] the use of reflected light technology for capillary refill assessment to provide deeper tissue penetration with less signal-to-noise ratio than transmitted infrared light, [2] the ability to significantly improve clinical outcomes without large changes to clinical workflow or provider practice, and [3] it can be used by individuals with minimal training and even in low resource settings to increase the utility of this technology. It should be noted that this perspective focuses on the utility of capillary refill for sepsis care, but it could be considered the next standard of care vital sign for assessment of end-organ perfusion. The ultimate goal for this sensor is to integrate it into existing monitors within the healthcare system.